The Relative Effectiveness of Empirical and Physical Models for Simulating the Dense Undercurrent of Pyroclastic Flows under Different Emplacement Conditions - Ogburn, Sarah E.; Calder, Eliza S. (Frontiers in Earth Science, 2017)
TITAN2D, VolcFlow, LAHARZ, and ∆H/L or energy cone models each employ different rheologies or empirical relationships and therefore differ in appropriateness of application for different types of mass flows and topographic environments. Previous work has focused on single-deposit comparisons of models. In this work, these models are used to recreate the inundation areas of the dense-basal undercurrent of all 13 mapped, land-confined, Soufrière Hills Volcano dome-collapse pyroclastic density currents (PDCs) emplaced from 1996-2010 to test the relative effectiveness of different computational models. Best-fit model results and their input parameters are compared with results using observation- and deposit-derived input parameters and those using empirically-derived input parameters from the FlowDat global database (Ogburn, 2012, 2014; Ogburn et al. 2016). Not only does this work provide a useful comparison of the operational aspects and behavior of various models, but it also enriches conceptual understanding of the dynamics of the PDCs themselves. Results indicate that TITAN2D is able to reproduce inundated areas well using flux sources, although velocities are often unrealistically high. VolcFlow is also able to replicate flow runout well, but does not capture the lateral spreading in distal regions of larger-volume flows. Both models are better at reproducing the inundated area of single-pulse, valley-confined, smaller-volume flows than sustained, highly unsteady, larger-volume flows, which are often partially unchannelized. LAHARZ is fast to run and can give a rough approximation of inundation, but there are problems with deriving the equation coefficients for PDCs and the designation of starting locations. The ∆H/L cone model is also very quick to run and gives reasonable approximations of runout distance, but does not inherently model flow channelization or directionality and thus unrealistically covers all interfluves.